Determination of the Inventory of Cassava Raw Materials UD Rezeky Baru Medan Based on the Economic Order Quantity (EOQ) Method - Silalahi, Anastasia Claresta; Siregar, Rosman (Talenta Publisher, 2022)
The need for an inventory control system basically arises because of problems faced by the company in the form of excess or shortage of company inventory. The EOQ (Economic Order Quantity) method is one of the inventory control methods used to determine the number of economic orders, namely the number of orders that meet the minimum total inventory cost. The purpose of this study was to determine the optimal amount of cassava raw material inventory at UD Rezeky Baru with the EOQ method and the comparison of the total cost of raw material inventory between costs according to the company and costs according to the EOQ method. Based on the results of calculations using the EOQ method, the optimal number of orders for cassava raw materials in 2019 is 18.722,62 kg. The total cost of raw material inventory using the EOQ method is Rp. 1.497.809,00, while according to the company, it is Rp. 9.467.640,00. The company can save on inventory costs by Rp. 7.969.830,00.